2022
DOI: 10.1007/s40670-022-01598-7
|View full text |Cite
|
Sign up to set email alerts
|

Communication Skills Training Using Remote Augmented Reality Medical Simulation: a Feasibility and Acceptability Qualitative Study

Abstract: Introduction Augmented reality (AR) has promise as a clinical teaching tool, particularly for remote learning. The Chariot Augmented Reality Medical (CHARM) simulator integrates real-time communication into a portable medical simulator with a holographic patient and monitor. The primary aim was to analyze feedback from medical and physician assistant students regarding acceptability and feasibility of the simulator. Methods Using the CHARM simulator, we created an advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The articles discussed in this section ( Multimedia Appendix 3 [ 32 , 36 , 40 - 42 , 47 - 51 , 58 , 62 , 69 ]) are divided based on nonsurgical contexts, which include clinical skills, autopsy, and sonography, and surgical contexts, which include procedure observation, tool-specific training, simulations, and intraoperative learning. Of note, one-third (6/19, 32%) of the articles that involved education have been described in the previous section and will be briefly mentioned in this section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles discussed in this section ( Multimedia Appendix 3 [ 32 , 36 , 40 - 42 , 47 - 51 , 58 , 62 , 69 ]) are divided based on nonsurgical contexts, which include clinical skills, autopsy, and sonography, and surgical contexts, which include procedure observation, tool-specific training, simulations, and intraoperative learning. Of note, one-third (6/19, 32%) of the articles that involved education have been described in the previous section and will be briefly mentioned in this section.…”
Section: Resultsmentioning
confidence: 99%
“…Hess et al [ 42 ] described a remote advanced cardiovascular life support simulation using Magic Leap One headsets distributed to second-year medical and physician assistant students. The HMDs used AR to display the holographic simulation apparatus (eg, patients, beds, and monitors) modulated by instructors, thereby allowing students to attend the simulation from their homes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the same quantitative measures are not consistently measured across these studies, favorable results in qualitative measurements such as ease of use and perceived efficacy have suggested that users are interested in using AR for remote learning. The role of AR in the education of trainees has also been previously investigated for anatomy [ 56 , 57 ], simulation [ 58 , 59 ], and social skills such as communication [ 32 , 60 ], with such applications increasingly appearing in the remote setting owing to interest in distance learning options [ 61 , 62 ]. Although our interviews reiterate the benefits of AR for medical trainees, they also suggest the use of AR in remotely teaching those without professions in health care.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 review of AR technology in emergency medicine found 8 papers related to telemedicine including remote surgical treatments, triage, and telementoring [ 27 ], whereas more recent papers have similarly described the use of AR in remote communication for emergency responders and procedures [ 28 , 29 ]. In addition to support for disaster medicine [ 30 ], AR has also been used in other remote contexts such as teleultrasound [ 31 ] and the teaching of teamwork during high-risk scenarios [ 32 ]. Although these studies suggest that emergency medicine as a specialty is poised to further explore the intersection of AR and telemedicine, there is paucity of literature on the perspectives of emergency telemedicine providers regarding the subject.…”
Section: Introductionmentioning
confidence: 99%